The Effectiveness of Podcast in Listening Class (Intensive Course Program) - Athena, Tera (JET ADI BUANA, 2016)
Based on Qasim and Fadda study on 2013, the result showed that the use of technology, that was Podcast, is able to contribute positive effect toward the students’ listening skill. The researcher used true-experimental and applied simple random sampling for 66 students into two groups. The way of researcher applied that sampling technique is through students’ attendance list number (even and odd number). The odd number was formed to be a new group. The researcher decided the odd number group as control group and the rest (even number) was an experimental group by throwing the coin. They saved the record in MP3 and USB. They could listen and choose the channel and topic as they like. Their preference to choose the issue will be one of the motivations to use Podcast. And the following step was filling the listening log as the media to evaluate what have they listened. After getting treatment for 8 weeks, the posttest has been analyzed by using SPSS showed that was Ho has been rejected and H1 was accepted. In other words, there was a positive effect from Podcast toward student’s listening skill. The Student’s perception is also good toward the using of Podcast. It can be shown from the results of questionnaire that were given to the 1A (odd number) students.